Various approaches to enhance the dissolution of Lornoxicam fast dissolving tablets prepared by using different categories of superdisintegrants: A comparative study - Acharya, A.; Kumar, G.B.K.; Goudanavar, P.; Dhakal, K. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: Recent developments in fast dissolving tablets have brought convenience in dosing to pediatric and elderly patients who have trouble in swallowing tablets.The main objective of the present study is to formulate fast dissolving tablet of Lornoxicam by direct compression method.Methods: Guar gum and crospovidone were used as natural and synthetic superdisintegrants respectively. Fast dissolving tablet of Lornoxicam were prepared by direct compression technique using three different approaches; superdisintegrant addition, sublimation, and solid dispersion.Results: IR and DSC studies showed no interaction between the drug and the excipients. All formulation showed disintegration time ranging from 16.09-42.54 second. Wetting time and disintegration time decreased by increasing the super disintegrant concentration from 2.5% to 5% w/w. Formulae L16 gave the best in- vitro disintegration and dissolution results, which would be due to swelling effect of Gaur gum and amorphization of the drug during the solid dispersion preparation.The best formulation L16 was subjected to stability testing for 3 month and results showed no significant change in appearance, hardness, drug content and dissolution profile of the tablets, hence tablet is stable throughout its stability studies.Conclusion: It was concluded that fast dissolving tablets of Lornoxicam were formulated successfully with desired characteristics which disintegrated rapidly; provided rapid onset of action; and enhanced the patient convenience and compliance.JMMIHS,2018;4(1):86-102